Blockade of leukocyte haptokinesis and haptotaxis by ketoprofen, diclofenac and SC-560 - Paskauskas, Saulius; Parseliunas, Audrius; Kerkadze, Vachtang; Nobiling, Rainer; Schmidt, Jan; Ryschich, Eduard (BMC immunology, 2011)
BACKGROUND: Nonsteroidal anti-inflammatory drugs (NSAID) represent a one of the most widely used anti-inflammatory substances. Their anti-inflammatory effects are mainly based on inhibition of cyclooxygenase. The potential direct effect of NSAID on leukocyte migration was poorly investigated. Using time-lapse microscopy and 96-well fluorescence-based assay, we studied the effect of three different NSAID, ketoprofen, diclofenac and SC-560, on leukocyte haptokinesis and haptotaxis in vivo and in vitro. - RESULTS: NSAID induced an immediate inhibiting effect on leukocyte migration both in vitro and in vivo. This effect was dose-dependent and was not restricted to a specific type of leukocytes. The inhibition of leukocyte migration by NSAID was partially re-stored after removal of inhibiting agent. Only complete blockade of leukocyte migration was accompanied by a strong reduction of [Ca(2+)]i. - CONCLUSIONS: NSAID strongly supress leukocyte migration. The results of the present study may have important clinical implications since blockade of leukocyte migration can be achieved after topical application of NSAID.
Gesehen am 22.09.2022